2022
DOI: 10.1109/access.2022.3185393
|View full text |Cite
|
Sign up to set email alerts
|

Toward Improving the Efficiency of Software Development Effort Estimation via Clustering Analysis

Abstract: Introduction:The precise estimation of software effort is a significant difficulty that project managers encounter during software development. Inaccurate forecasting leads to either overestimating or underestimating software effort, which can be detrimental for stakeholders. The International Function Point Users Group's Function Point Analysis (FPA) method is one of the most critical methods for software effort estimation. However, the practice of using the FPA method in the same fashion across all software … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…This research might have revealed variations in the level of AI awareness and acceptance within company employee culture, finding that investing in AI talent and skills positively influences AI adoption. Employee buy-in and readiness for AI-driven changes are vital, as was confirmed in [63]. Consequently, companies with a culture of curiosity and adaptability to change that fosters AI innovation are more likely to succeed in AI integration [64].…”
Section: Key Findings and Insightsmentioning
confidence: 87%
“…This research might have revealed variations in the level of AI awareness and acceptance within company employee culture, finding that investing in AI talent and skills positively influences AI adoption. Employee buy-in and readiness for AI-driven changes are vital, as was confirmed in [63]. Consequently, companies with a culture of curiosity and adaptability to change that fosters AI innovation are more likely to succeed in AI integration [64].…”
Section: Key Findings and Insightsmentioning
confidence: 87%
“…As a downside, their work was limited to single linkage hierarchical clustering without the existence of ordinal and binary variables. Van Hai et al (2022) considered several alternative clustering methods to estimate effort (not cost) of software projects. They used five categorical variables and clustered using k-means, both for the variables collectively and separately to compare those approaches with not clustering the data.…”
Section: Cost Estimation Approaches Using Clustering and Splinesmentioning
confidence: 99%
“…These methods have been used to increase the precision of cost and effort estimation [17]. The choice between these strategies depends on several variables, including the accessibility of data, the complexity of the project, and the expertise that is available inside the organization.…”
Section: Computational Intelligencementioning
confidence: 99%